A espetacularização da fé na Igreja Apóstolica Plenitude do Trono de Deus - Oliveira, Priscilla Luciane Bastos (2017)
The guiding proposition of this study is the analysis of the interconnection between the phenomenon of spectacularization, result of the cultural industry production, and the neopentecostal religious group. Among the neopentecostal churches, which use the spectacle of faith, we chose as the object of study the Igreja Apostólica Plenitude do Trono de Deus, founded by the apostle Agenor Duque and the bishop Ingrid Darakdjian Medeiros. We propose in this research to identify the mechanisms by which the spectacularization of faith is used by denominational leaders in order to reach and retain loyalties and to gain legitimacy in society. The research was organized through non-participant observation in lócus, interviews, investigations in the communication channels and in websites. In the religious practices of the Igreja Apostólica Plenitude do Trono de Deus, it was possible to perceive its relation with religious entrepreneurship, being the spectacularization of faith, a significant factor for its expansion in the religious field. We conclude, then, that the leaders of the Igreja Apostólica Plenitude do Trono de Deus use the spectacularization proposed by Debord (2011) in order to attract adherents to the denomination and to promote its legitimacy in the Brazilian religious scene.